2022
DOI: 10.1108/apjml-05-2021-0368
|View full text |Cite
|
Sign up to set email alerts
|

Chief marketing officers' future focus and firms' sustainability marketing commitment

Abstract: PurposeThis study examines a moderated moderation model in which the hardiness of chief marketing officers (CMOs) moderates the relationship between CMOs' future focus and firms' sustainability marketing commitment (SMC), and this moderating effect is moderated by CMOs' proactive personality.Design/methodology/approachA sample of 298 CMOs of firms in Vietnam was surveyed to collect data. Confirmatory factor analysis was employed to validate the measures of the constructs used in the model and structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…Long-term business direction hinged on sustainability development can provide viability of enhanced industry performance alongside implementation of environmental strategies and solidifying SMC (Bamgbade et al, 2017). Previous studies have observed that positive attitude in managers has favorable impact on environmental behavior and taking a proactive stance in the implementation of environmental strategies is more influential and has positive effect on SMC (Thu and Tho, 2023). Therefore, owners and managers should explicitly show strong commitment to motivating employees to improve service capabilities and service quality to amplify service attractiveness as competitive advantage.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Long-term business direction hinged on sustainability development can provide viability of enhanced industry performance alongside implementation of environmental strategies and solidifying SMC (Bamgbade et al, 2017). Previous studies have observed that positive attitude in managers has favorable impact on environmental behavior and taking a proactive stance in the implementation of environmental strategies is more influential and has positive effect on SMC (Thu and Tho, 2023). Therefore, owners and managers should explicitly show strong commitment to motivating employees to improve service capabilities and service quality to amplify service attractiveness as competitive advantage.…”
Section: Managerial Implicationsmentioning
confidence: 99%